Pelatihan Pengembangan Inovasi Bioaktivator Untuk Meningkatkan Kualitas Pangan Organik Berbasis Sistem Pertanian Organik - Joko Sulistyo; Irra Chrisyanti Dewi; Adrie Oktavio (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2024)
One effort to produce organic food products is to increase the productivity of organic farming using bioactivators to create a conducive environment to support the growth and fertility of soil microbiota, protect the surrounding environment, and increase soil fertility. Organic food is managed in such a way as to realize sustainable productivity. Therefore, the provision of bioactivators as decomposers of organic matter in the soil can facilitate the maximum presence of nutrients, water and air. Trial of the use of bioactivators consisting of a consortium of microorganisms as agents for decomposing organic matter in soil. The research results show that bioactivators can repair the chemical, physical, and microbiological properties of soil. The use of bioactivators does not cause the heavy metals accumulation in water, soil, and plant growth. As a decomposer of soil organic matter, bioactivators meet the minimum of technical requirements. The use of bioactivators as decomposers of soil organic matter to support organic agricultural commodities so as not to have a negative impact on the accumulation of heavy metals in soil, water and the surrounding environment.